Optimal Design of Integrated Heat Pipe Air-Cooled System Using TLBO Algorithm for SiC MOSFET Converters - Maryam Alizadeh; Romina Rodriguez; Jennifer Bauman; Ali Emadi (IEEE Open Journal of Power Electronics, 2020)
Optimal thermal management system design is critical for power electronic converters to ensure the reliability of power semiconductor switches. Medium power density inverter systems are often air-cooled to ensure an efficient and cost-effective thermal management solution. In addition, using heat pipes as the heat transfer medium between the heat sources and the heat sink can provide lower volume for the entire inverter. This paper investigates the effectiveness of Teaching Learning Based Optimization (TLBO) for finding the optimal forced-air heat sink with heat pipe cooling system to achieve higher fan efficiency and lower inverter packaging volume. The optimal design is found utilizing commercially available fans and heat pipes. The TLBO design optimization is also compared to the highly implemented Particle Swarm Optimization (PSO) and it is found that TLBO uses 20 times fewer iterations than PSO to converge, and that the TLBO results are more robust for different design constraints.